Process improvement using Six Sigma : a DMAIC guide - Shankar, Rama, 1956- (ASQ Quality Press, 2009)
"The purpose of this book is to provide the practitioner with the necessary tools and techniques with which to implement a systematic approach to process improvement initiatives using the Six Sigma methodology."--Jacket